2022
DOI: 10.3126/jcmsn.v18i3.47444
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Pattern of Antibiotics in ENT Outpatients of Tertiary Care Hospital in Bharatpur, Nepal

Abstract: Introduction: Upper respiratory tract infection (URTI) like pharyngitis, tonsillitis, sinusitis, laryngitis and otitis media are the most common infections encountered in ENT outpatients. As these infections are caused by the microorganism they should be treated with the antimicrobial agents. The aim of this study was to determine the prescribing pattern of antibiotics in ENT outpatients of tertiary Care Hospital in Bharatpur, Nepal. Methods: It was prospective observational study which was carried out in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Similar to this study, previous studies have demonstrated that the risk of SSI considerably rises with contamination level. 16,17,22 Various risk factors were assessed for their association with surgical site infections. Smoking, ASA grade, diabetes, comorbidities, hemoglobin levels, white blood cell count, and albumin levels were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to this study, previous studies have demonstrated that the risk of SSI considerably rises with contamination level. 16,17,22 Various risk factors were assessed for their association with surgical site infections. Smoking, ASA grade, diabetes, comorbidities, hemoglobin levels, white blood cell count, and albumin levels were evaluated.…”
Section: Resultsmentioning
confidence: 99%